2010
DOI: 10.1103/physrevb.82.104427
|View full text |Cite
|
Sign up to set email alerts
|

Current-induced vortex dynamics and pinning potentials probed by homodyne detection

Abstract: Using a homodyne detection scheme, we show that we can determine the polarity and chirality of a magnetic vortex in an asymmetric magnetic disk as well as the resonance frequency and phase shift of the dynamic vortex gyration excited by a spin-polarized current. From systematic phase measurements, we deduce the relative contributions of the spin torque and the Oersted field, which is found to dominate the excitation. Local pinning sites in the disk lead to an increased resonance frequency and a reduced amplitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…Therefore, the vortex state is formed by reducing the demagnetization energy by increasing the exchange coupling energy for in-plane magnetic materials. There are many researches on the vortex dynamics with the ac-and dc-external fields and spin polarizing currents [4][5][6][7] as well as with the devices [8,9]. However, all researches regarding the vortex states are considered only in the in-plane magnetic anisotropy (IMA) materials.…”
Section: Introductionsmentioning
confidence: 99%
“…Therefore, the vortex state is formed by reducing the demagnetization energy by increasing the exchange coupling energy for in-plane magnetic materials. There are many researches on the vortex dynamics with the ac-and dc-external fields and spin polarizing currents [4][5][6][7] as well as with the devices [8,9]. However, all researches regarding the vortex states are considered only in the in-plane magnetic anisotropy (IMA) materials.…”
Section: Introductionsmentioning
confidence: 99%
“…This study is significant as it was the first to demonstrate the direct observation of gyrotropic motion of the vortex core in the time domain. Other authors have shown similar time-resolved measurements in elongated rectangular magnetic elements with cross-tie domains [214], in an asymmetric magnetic disk using current-induced vortex dynamics [222] and nonlinear nongyrotropic motion in permalloy disks as a function of an applied magnetic field [223,224]. In Fig.…”
Section: X-ray Magnetic Circular Dichroism (Xmcd) and X-ray Photoemismentioning
confidence: 57%
“…Thus, a vortex needs much stronger fields to be pushed towards the boundaries of the structure. 19,24,26 In the graph showing the core position for all field strengths and angles, see Fig. 5(b), another effect of the open junction can be seen.…”
mentioning
confidence: 91%